Pemanfaatan Kali Mati Sebagai Media Pembuatan Kolam Waring di Desa Iringmulyo, Metro Timur, Kota Metro - Dwi Irawan; Yusuf Amran (Universitas Mathla'ul Anwar Banten, 2016)
Based on situation analysis, client problem and joint discussion result, the priority problem that experienced by inhabitants of RT. 26 and RT. 27 Iringmulyo Village, sub-district of Metro Timur, Metro City is untidiness of dead river that is not utilized and only used as laystall by some inhabitants. The promoted approach methods to solve this clien problem are: cleaning dead river, building nets fish pond, and provision of venture capital to inhabitants. By conducting these IbM program, it is expected for comfort and cleanliness of environment around river, increasing of inhabitant’s economic income by fish cultivation. The foundational of problem solving is to reduce environmental pollution and to prohibit inhabitant for throwing rubbish into dead river and enhancement of inhabitant prosperity. This activity has made dead river cleans, fishing group (Pokdakan) is formed named “Metro Bintang Timur” that has legality evidence, 6 nets fish pond is built where main foundation is plastic drum where if flood comes, the nets will float and unstuck. The pokdakan is given capital of fingerlings of catfish and fish feed for development and mentoring phase till the harvest time.